Group Exhibition-Is this the Time for Art? Modern Art Museum Orebro Konstall - Antoniou, Klitsa (My University, 2026)
Is this the Time for Art? Modern Art Museum Orebro Konstall, Sweden. Atlantropa Series: But the Sea Kept Turning Blank Pages Looking for History Curated by Erik Berggren